Staphylococcus aureus e resistência à oxacilina em jalecos de profissionais de saúde de um hospital geral - Silva Junior, Vanderlei Amaro da (2021)
The health team's clothing can play the role of a reservoir for pathogens, contributing to the spread of microorganisms. Pathogens can survive, depending on conditions, for up to 90 days in tissues. Specifically, Staphylococcus aureus and its phenotype of resistance to oxacillin are of extreme concern in health care services, as they can be spread by the hands of professionals and various fomites, including lab coats. The aim of this study was to analyze the use and handling of lab coats by health professionals and to identify the presence of Staphylococcus aureus and its resistance to oxacillin. This is a descriptive, cross-sectional study with a quantitative approach carried out with health professionals working in health care units. hospitalization of a philanthropic hospital in the interior of the state of Mato Grosso do Sul, which is a reference for 10 municipalities in the state. The study allowed us to verify that among the participants, most use the lab coat only in their work sector and do not use it outside the hospital, in public environments. As for the change of the coat, it takes place every shift. Most professionals carry out their own hygiene of their coats, and the percentage of washing frequency at each shift increased during the pandemic. As for the presence of Staphylococcus aureus and its resistance to oxacillin, it was observed that it was higher in coats of employees working in the medical-surgical clinic. The data reinforce the importance of lab coats as a means of sheltering pathogenic agents within health services. It is essential to adopt strategies to minimize this impact, ranging from the training of health professionals, with aspects of biosafety, with a view to promoting professional awareness for the proper use of lab coats.